Suggerimenti di lettura - Sperindio, Loriana; Degasperi, Sara; Scrivano, Fabrizio; Lazzarini, Carmine; Bo, Mariella; Lazzarini, Carmine; Macario, Giorgio; Risse, Stefanie; Scanarotti, Roberto; Manenti, Elena (Autobiografie. Ricerche, pratiche, esperienze, 2020)